2013
DOI: 10.3324/haematol.2013.091702
|View full text |Cite
|
Sign up to set email alerts
|

Primary cold agglutinin-associated lymphoproliferative disease: a B-cell lymphoma of the bone marrow distinct from lymphoplasmacytic lymphoma

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nCAD diagnosed in the time period between 1995 and 2012 were studied. There were 36 women and 18 men with an age range of 40-92 (median 73) years. All patients had a clinical history of CAD with a variable degree of anemia, a positive C3d-specific direct antiglobulin test and a cold agglutinin titer in excess of 64. Monoclonal IgM had been detected in the serum of all patients by agarose electrophoresis and immunofixation. None of the patients had lymphadenopathy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 41 publications
1
124
1
4
Order By: Relevance
“…Previously, we demonstrated that CAD is caused by a low-grade clonal B-cell lymphoproliferative disease of the bone marrow with a typical histology that is different from lymphoplasmacytic lymphoma and, accordingly, does not display the MYD88 L265P mutation. 1 Almost all patients display circulating monoclonal antibodies encoded by the IGH gene V4-34. The framework region 1 (FR1) of IGHV4-34 encodes Gln 6 -Trp 7 (QW) and Ala 24 -Val 25 -Tyr 26 (AVY) sequences that determine I antigen-binding.…”
mentioning
confidence: 99%
“…Previously, we demonstrated that CAD is caused by a low-grade clonal B-cell lymphoproliferative disease of the bone marrow with a typical histology that is different from lymphoplasmacytic lymphoma and, accordingly, does not display the MYD88 L265P mutation. 1 Almost all patients display circulating monoclonal antibodies encoded by the IGH gene V4-34. The framework region 1 (FR1) of IGHV4-34 encodes Gln 6 -Trp 7 (QW) and Ala 24 -Val 25 -Tyr 26 (AVY) sequences that determine I antigen-binding.…”
mentioning
confidence: 99%
“…Autoimmune disorders may precede or follow the diagnosis of CLL 2. In our case, the cold agglutinin and the increased lymphocytes were discovered at the time of the diagnosis.…”
Section: Reportmentioning
confidence: 50%
“…The findings are similar to those of a recent study showing that cold agglutinin associated B-cell lymphoproliferative disorders lack the MYD88 L265P mutation. 55 These results suggest that lymphomas associated with cold agglutinin disease arise through a different pathogenetic mechanism than typical lymphoplasmacytic lymphoma, and that these may be considered to represent distinct entities. However, this must be further clarified as cold agglutinins have been reported in one study in 27% of MYD88 L2565P mutated lymphoplasmacytic lymphoma.…”
Section: F Hamadeh Et Almentioning
confidence: 86%